PENGARUH UKURAN PERUSAHAAN TERHADAP INTELLECTUAL CAPITAL DISCLOSURE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ming Chen (Catholic University Musi Charitas, 2019)
The purpose of this study is to test empirically whether the size of the company influences the disclosure of intellectual capital. In this study variables, the size of the company is proxies by market capitalization, whereas the disclosure of intellectual capital is measured by the ICD Index which amounts to 25 items. The sample of this study is manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2017. This study uses a simple regression analysis and uses SPSS 22 tools. The results of this study are the size of the company influences the disclosure of intellectual capital.